Legal Review of Perpetrators of Schizophrenic Psychiatric Disorders (Legal Review of Article 44 of Law Number 1 of 2023 In The Crime of Murder) (Case Study Decision Number: 181/Pid/2024/PT DKI) - Anggarita, Levy Rizka; Sumampouw, Wuri; Asyharuddin, Asyharuddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
(1) Schizophrenia is a serious mental disorder in which the sufferer has difficulty distinguishing between delusion and reality. This condition is commonly characterized by unusual behaviors such as delusions and hallucinations. For this reason, individuals experiencing such symptoms are often referred to as